What is left and what is right? Spatial position as a context for conceptual processing - Tonković, Mirjana psihologinja (Array, 2013)
Abstract concepts are often described in terms of spatial dimensions. For example, time is represented on a horizontal line with past on the left, and future on the right. Mental number line goes form left to the right. Some studies indicate that horizontal axis is also used to describe power and affect. Theories of grounded cognition assume that metaphors describe the way in which concepts are represented in memory. Aim of this research was to test the assumptions of grounded cognition theories for abstract concepts, and to explore representation of abstract concepts on horizontal line as implied by metaphors. In first experiment we explored influence of spatial position of different word categories on speed in semantic decision task. Pairs of words were presented on a horizontal line one next to the other. Participants were faster to respond to pairs of words related to quantities when small quantities were presented on the left and large on the right. Second experiment examined influence of spatial position on speed of detection of neutral object after presentation of words from different categories. Participants were slower to identify object that appeared in position congruent with the metaphorical representation of previously presented word from categories of time and quantities. Results support the idea of perceptual processes being active during processing of concepts related to time and quantities.